CFD modeling of ultrasonic wave propagation in non-consolidated porous media: article / Wan Muhammad Hafidz Wan Alia - Wan Alia, Wan Muhammad Hafidz (2019)
Produce sand or oil sludge production is one of major solid waste and it needs to be removed to avoid future problem. Ultrasonic cleaning attracts main company in oil and gas industry due to the precision cleaning thus shown strong promise, but distance from transducer to material used, frequency used, diameter and wall thickness of material to need to be determine in order to enhance high efficiency cleaning. A cleaning reactor was designed with the ultrasound transducer installed at the bottom of the reactor. The pressure distribution, temperature, flow and effect on porous media were studied in this paper. Flow behavior of liquid was investigated using CFD calculation and simulation by ASNYS FLUENT software. Liquid in the reactor was exposed with sound waves with frequency of 68 kHz from transducer installed. Comparison between simulation results and experimental result was evaluated in term of pressure and cavitation field also temperature distribution. The modeling results showed the pressure and cavitation fields, temperature distribution was aligned with experimental values. Velocity vectors were used to investigate the mixing of the liquid exposing the ultrasound waves. The modelling shows flow behavior of 20kHz, 68kHz and 150kHz frequency, and velocity factor from 68kHz ultrasonic transducer used is compared. Porous media condition when transducer us activated also investigated in this project. Last but not least, some suggestion can be done to improve the efficiency of cavitation process when transducer is activated to enhance more cleaning activity in the designed reactor.